Effect of carbonates fluorination on the properties of LiTFSI-based electrolytes for Li-ion batteries. (10th April 2015) - Bolloli, Marco; Alloin, Fannie; Kalhoff, Julian; Bresser, Dominic; Passerini, Stefano; Judeinstein, Patrick; Leprêtre, Jean-Claude; Sanchez, Jean-Yves
ABSTRACT: Electrolyte compositions based on LiTFSI dissolved in fluorinated linear and cyclic carbonates were characterized regarding their transport and thermal properties, viscosity, solvation ability, electrochemical stability towards oxidation, as well as their ability to inhibit the aluminum current collector corrosion. As a result of the thorough investigation, different binary mixtures were prepared, which offer beneficial properties in terms of aluminum current collector protection and provide optimized transport properties. The use of LiTFSI as electrolyte salt rather than the state-of-the-art lithium salt, LiPF6, enables substantial improvements with respect to safety, while maintaining high performance liquid electrolyte.